Determinants of Agricultural Household Business Terms of Trade in Indonesia: Empirical Evidence of Nonlinear Autoregressive Distributed Lag Model Application - Arintoko, Arintoko; Sambodo, Herman; Priyono, Rakhmat (International Journal of Economics and Financial Issues, 2025)
This study analyzes the asymmetric effects of changes in world oil and fertilizer prices, exchange rate, price index, and agricultural credit on agricultural household business terms of trade (AHBTOT) in Indonesia. The analysis in this study applies the Nonlinear Autoregressive Distributed Lag (NARDL) model to monthly data from January 2014 to December 2023. The results of the study show that the decline in world fertilizer prices, which is passed on to the decline in domestic fertilizer prices, significantly increases AHBTOT, while domestic inflation decreases AHBTOT. Meanwhile, the decline in agricultural credit significantly decreases AHBTOT. In the short run, the weakening of the exchange rate and the decline in agricultural credit significantly decrease AHBTOT. To support the welfare of farmers, the feasibility of agricultural household businesses is absolutely necessary. The government should be able to guarantee low fertilizer prices along with the still high import of fertilizers through subsidies and distribution that ensure easy access for farmers to obtain cheap fertilizers. Meanwhile, inflation control by the government and access to agricultural credit can encourage increasing AHBTOT. Stabilizing inflation and the rupiah exchange rate through monetary policy will certainly provide support for improving the performance of agricultural household businesses.